Computer Aided Surgery - Fujie, Masakatsu; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book presents the latest research advances in the theory, design, control, and application of robot systems intended for a variety of purposes such as manipulation, manufacturing, automation, surgery, locomotion, and biomechanics. Several chapters deal with fundamental kinematics in nature, including synthesis, calibration, redundancy, force control, dexterity, inverse and forward kinematics, kinematic singularities, and over-constrained systems. This book is a compilation of the extended versions of the very best papers selected from the many that were presented at the Asian Conference on Computer-Aided Surgery held September 16-18, 2013, in Tokyo, Japan (ACCAS 2013).
Brain Activity Analysis for the Configurational Determination of Surgical Manipulation and Endoscope -- 3D Tracking of Respiratory Liver Movement by a Robot Assisted Medical Ultrasound -- Development of a Robot Assisted Intubation System and Parameter Optimization -- Development of a Dexterous Manipulator for Single Port Access Surgery -- Motion Control of a Master-Slave Minimally Invasive Surgical Robot Based on the Hand-Eye-Coordination -- Liver Function Region Segmentation in Nuclear Medicine Using Mean Shift and Level Set Methods -- A Pilot study of the physiological assessment of 3D camera using 128ch EEG -- Self-Registration of Ultrasound Imaging Device to Navigation System using Surgical Instrument Kinematics in Minimally -- An Application of Robot Arm for Dynamic Field of View Expansion During Laparoscopy -- Evaluation of Safety and Performance in Robots for Knee Replacement Surgery Based on Standards Invasive Procedure -- Fast Surgical Algorithm for Cutting with Liver Standard Triangulation Language Format Using Z-buffers in Graphics Processing Unit -- Evaluation of Elapsed Times for Surgical Workflow of Deep Brain Stimulation: A Preliminary Report.
Keywords: Biomedical engineering; Image processing -- Digital techniques; Computer vision; Radiology; Surgery; Biomedical Engineering and Bioengineering; Computer Imaging, Vision, Pattern Recognition and Graphics; Radiology; General Surgery